Reasons for inpatients not to seek clarity at Dr George Mukhari Academic Hospital, Pretoria - Langalibalele H. Mabuza; Olufemi B. Omole; Indiran Govender; John V. Ndimande (AOSIS, 2014)
Background: Healthcare practitioners should provide patients with information regarding their clinical conditions. Patients should also feel free to seek clarity on information provided. However, not all patients seek this clarity. Objectives: To explore the reasons inpatients gave for not seeking clarity on information that was received but not understood. Methods: This was a qualitative arm of a larger study, titled 'Are inpatients aware of the admission reasons and management plans of their clinical conditions? A survey at a tertiary hospital in South Africa', conducted in 2010. Of the 264 inpatients who participated in the larger study, we extracted the unstructured responses from those participants (n = 152) who had indicated in the questionnaire that there was information they had not understood during their encounter with healthcare practitioners, but that they had nonetheless not sought clarity.Data were analysed thematically. Results: Themes that emerged were that inpatients did not ask for clarity as they perceived healthcare practitioners to be 'too busy', aloof, non-communicators and sometimes uncertain about patients' conditions. Some inpatients had unquestioning trust in healthcare practitioners,whilst others had experiences of bad treatment. Inpatients had poor self-esteem, incapacitating clinical conditions, fear of bad news and prior knowledge of their clinical conditions. Some inpatients stated that they had no reason for not seeking clarity. Conclusion: The reasons for not seeking clarity were based on patients' experiences with the healthcare practitioners and their perceptions of the latter and of themselves. A programme should be developed in order to educate inpatients on effective communication with their healthcare practitioners.